Preparation of Principal for School Change: A Singapore Perspective - Pokharel, Babin (Journal of Education and Vocational Research, 2013)
This paper examines the understanding of the educational leadership process and the exploration of systematic preparation of private school principal in order to cope with future school change. Leading through change in education is a must in 21st century. Various contexts determine the change in leadership process. In schools, principal needs to be prepared in order cope with contextual changes. Changes in school can be seen various contexts such as cultural, technological, policy level, outbound competitions so on and so forth. School principal are the most important catalyst in the construction of new and innovative leadership practices that enhance the change process. Specifically, it presents the findings from the case of four private schools principal in Singapore through their storytelling. This paper includes an overview of the study and a discussion of growing themes related to the leadership process of the principals and their preparation strategy for a school change. The results from this study indicate how school principal prepare themselves for future and school change taking the entire internal and external environment into consideration.